Development of a low-cost non-invasive neurostimulator for applications in post stroke hemiplegics. (1st September 2010) - Sabut, S.K.; Manjunatha, M.; Kumar, Ratnesh; Lenka, P.
A noninvasive low-cost, programmable single channel stimulator with generating various patterns of waveforms for Functional Electrical Stimulation (FES) applications has been developed. The prototype is small, battery-operated, and flexible for various clinical applications in home and in clinics. A microcontroller is heart of the stimulator used for generating rectangular waveforms and natural pattern of Tibialis Anterior (TA) muscle waveform and controls the pulse rate and frequency. This FES system is used for rehabilitation of persons who suffered a central nervous system lesion and lost voluntary control over muscles necessary for standing, walking, hand-grasp etc., and to regain lost functions.